2017
DOI: 10.3390/polym9080374
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Nanocellulose from Side-Streams of Kombucha Beverages Production: Preparation and Physical-Chemical Properties

Abstract: Abstract:We focused on preparing cellulose nanofibrils by purification, separation, and mechanical treatment of Kombucha membranes (KM) resulted as secondary product from beverage production by fermentation of tea broth with symbiotic culture of bacteria and yeast (SCOBY). We purified KM using two alkaline solutions, 1 and 4 M NaOH, which afterwards were subjected to various mechanical treatments. Transmission electron microscopy (TEM), scanning electron microscopy (SEM), dynamic light scattering (DLS), X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
90
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 70 publications
6
90
0
5
Order By: Relevance
“…One of the most popular natural and biodegradable polymers is cellulose, the main constituent of wood and cotton (Dima et al 2017;Keshk 2014;Seder-avičiūt_ e et al 2019). It is abundantly present in the ecosystem, which makes it easy to obtain-by merely using various plants, as it is their main component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most popular natural and biodegradable polymers is cellulose, the main constituent of wood and cotton (Dima et al 2017;Keshk 2014;Seder-avičiūt_ e et al 2019). It is abundantly present in the ecosystem, which makes it easy to obtain-by merely using various plants, as it is their main component.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the above into consideration, a more environmentally friendly solution may be the use of bacteria-derived cellulose (BC) (Brown 1886). BC is a porous biopolymer possessing a knit-like structure that is produced in the fermentation process by various microorganisms, like bacteria of the genera Gluconobacter or Agrobacterium (Dima et al 2017;El-Saied et al 2004;Gao et al 2019;Matthysse et al 1995;Bandyopadhyay et al 2018). The interest in bacteria-derived cellulose was aroused because of its exceptional physicochemical properties, like high crystallinity, high specific surface area, high elasticity, relatively high mechanical strength in the wet state, hydrophilicity and excellent biocompatibility (Abitbol et al 2016;Campano et al 2015;Habibi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Kombucha drink is popular in many countries and many benefits of consuming this drink have been reported [8]. Some research found where purification process and structure of bacterial cellulose obtained from Kombucha was investigated [9,10].…”
Section: Introduction mentioning
confidence: 99%
“…HS are naturally synthetized in reactions involving hydrophilic, hydrophobic, ionic, and donor-acceptor intermolecular forces of different biomassderived components, such as amino acids, carbohydrates, lignins, and pectines [1]. Humins, as macromolecular associations, and fulvic acids, as lower-molecular-weight compounds, present appealing properties that make them interesting for use in formulations with potential biostimulant effects for plants development [2].Nanoemulsions were prepared by vigorously mixing on a magnetic plate a solution of 0.2% bacterial nanocellulose (BNC) previously obtained by purification and microfluidization [3], with 1% or 3% chitosan dissolved in 1% acetic acid, a 1% alginate solution, and a liquid phase containing humic and fulvic compounds obtained from un-catalyzed and catalyzed hydrothermal processes of lignocellulosic biomass. For catalyzed hydrothermal conversion (HTC) process, a Cu-Pd-Ce/γAl2O3 catalyst was used.…”
mentioning
confidence: 99%
“…Nanoemulsions were prepared by vigorously mixing on a magnetic plate a solution of 0.2% bacterial nanocellulose (BNC) previously obtained by purification and microfluidization [3], with 1% or 3% chitosan dissolved in 1% acetic acid, a 1% alginate solution, and a liquid phase containing humic and fulvic compounds obtained from un-catalyzed and catalyzed hydrothermal processes of lignocellulosic biomass. For catalyzed hydrothermal conversion (HTC) process, a Cu-Pd-Ce/γAl2O3 catalyst was used.…”
mentioning
confidence: 99%